2016
DOI: 10.17363/sstb.20161816492
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Trust in Hospitals: A Model Study

Abstract: Öz: Bu çalışma sağlık çalışanlarının örgütsel güven düzeylerini belirlemek, örgütsel güven düzeyi ile sosyodemografik özellikleri arasındaki ilişkilerin belirlenmesine yönelik hazırlanmıştır. Araştırma sağlık çalışanlarının sosyo-demoğrafik özeliklerini tanımlayan bir anket formu ile örgütsel güven ölçeğinden oluşmuş tanımlayıcı bir çalışmadır. Veriler, araştırmaya katılmaya istekli, iki özel hastaneden, toplamda 534 sağlık çalışanından elde edilen, 409 adet geçerli anket ile yapılmıştır. Örneklem seçimi tesad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Past interaction, openness, autonomy, credibility, competence, and organizational culture have been reported in the literature to be the main factors that have a major influence on organizational trust (Demircan and Ceylan, 2003). However, some sources have stated that organizational trust is affected by age, gender, education level, and job satisfaction (Erdoğan and Yıldırım, 2017;Gün and Söyük, 2017;Şengün and Söyük, 2016;Vagharseyyedin, 2016;Velickovic et. al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past interaction, openness, autonomy, credibility, competence, and organizational culture have been reported in the literature to be the main factors that have a major influence on organizational trust (Demircan and Ceylan, 2003). However, some sources have stated that organizational trust is affected by age, gender, education level, and job satisfaction (Erdoğan and Yıldırım, 2017;Gün and Söyük, 2017;Şengün and Söyük, 2016;Vagharseyyedin, 2016;Velickovic et. al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, in one study, the "Trust in the executive" subscale score of nurses with 1-9 years of work experience was found to be relatively higher, although not statistically significant (Basit and Duygulu, 2018). Şengün and Söyük (2016) reported that healthcare workers who had 1-5 years of work experience had the highest mean score of trust in the organization. Furthermore, it was noted in another study that as the work duration increased, the mean score of organizational trust decreased (Gün and Söyük, 2017).…”
Section: Discussionmentioning
confidence: 99%